Faktor-faktor yang berhubungan dengan kejadian peningkatan kadar gula darah pada pasien TBC (tuberkulosis) - Elsa, Aprina; Antoro, Budi; Sari, Nova Nurwinda (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Tuberculosis (TBC) is a contagious infectious disease caused by Mycobacterium tuberculosis, which primarily affects the lungs but can also impact body metabolism, including increasing blood glucose levels. Factors such as age, duration of medication, and nutritional status are suspected to contribute to this condition. Purpose: To identify the factors associated with increased blood glucose levels in TBC patients at Way Halim Community Health Center, Bandar Lampung, in 2025. Method: This research employed a quantitative approach with a descriptive analytic design and Chi-Square test analysis, involving 51 respondents. Results: Data were collected through observation and medical documentation. The results showed that the majority of respondents were over ≥ 45 years old (64.7%), had a medication history of more than ≥2 (66.7%), and experienced elevated blood glucose levels ≥140 mg/dL (46.8%). There were significant associations between age (p=0.003), duration of medication (p=0.007), and body mass index (p=0.032) with increased blood glucose levels in TBC patients. Conclusion: The study concludes that advanced age, prolonged medication use, and excessive nutritional status are significantly associated with elevated blood glucose levels. Therefore, TBC management should consider metabolic factors to prevent further complications.   Keywords: Age; Blood Glucose Levels; Body Mass Index; Treatment Duration; Tuberculosis.   Pendahuluan: Tuberculosis (TBC) merupakan penyakit infeksi menular yang disebabkan oleh Mycobacterium tuberculosis dan tidak hanya menyerang paru-paru, tetapi juga dapat mempengaruhi metabolisme tubuh seperti peningkatan kadar gula darah. Faktor usia, lama minum obat, dan status gizi diduga turut berperan dalam kondisi tersebut. Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan kejadian peningkatan kadar gula darah pada pasien TBC di Puskesmas Way Halim Kota Bandar Lampung tahun 2025. Metode: Pendekatan kuantitatif dengan desain deskriptif analitik dan teknik analisis uji Chi-Square, melibatkan 51 responden dengan data diperoleh melalui observasi dan dokumentasi medis. Hasil: Mayoritas responden berusia ≥ 45 tahun (64.7%), memiliki riwayat minum obat  ≥ 2 bulan (66.7%), dan mengalami peningkatan kadar gula darah ≥ 140 mg/dL (46.8%). Terdapat hubungan yang signifikan antara usia (p=0.003), lama minum obat (p=0.007), dan indeks massa tubuh (p=0.032) dengan peningkatan kadar gula darah pada pasien TBC. Simpulan: Faktor usia lanjut, lamanya konsumsi obat, dan status gizi berlebih berhubungan signifikan dengan peningkatan kadar gula darah, sehingga penanganan TBC perlu mempertimbangkan faktor-faktor metabolik untuk mencegah komplikasi lebih lanjut.   Kata Kunci: Indeks Massa Tubuh; Kadar Gula Darah; Lama Pengobatan; Usia.